As práticas educativas digitais nos museus virtuais - Vasconcelos, Karla Colares (2014)
The research investigated the virtual museum as a teaching tool in digital educational practices and their contribution to the construction of memory and how digital sources for acquiring knowledge. To develop this goal we use the qualitative research strategy and how the case study research because it allows analyzing an individual phenomenon by providing an overview of similar phenomena (Yin, 2005). As the research took place in virtual environments, virtual ethnography was the basis for investigation in Internet environments. The concepts of Cibercultara were developed; Digital memory; Digital and Museology Educational Practices. Armed with this clarity, we did a survey of registered virtual museums in Brazilian Institute of Museums - IBRAM and sequentially classify Brazilians virtual museums and analyzed according to the didactic potential of each. Data collection was performed by daily digital board, which answered the question: How does the phenomenon of virtual museums is considered a social contribution of digital memory and can be a teaching tool in digital educational practices? The resources used in this research were: a bibliographic exploration, digital document (image, video, text, links) and the daily digital board. The results allowed us to reflect and meaningful learning to know and understand the phenomenon of education within the digital communication and information technologies that are allocated in cyberspace. Thus, we can understand how these technologies help us in view of the spread of memory, be it collective or social and migration of information - memories - to the clouds. The relevance of the study of memory was presented during the research, it was found that a museum guard social memory through the speech of ordinary people who can record their history in the museum. Thus we realize that in a direct way the Digital Educational Practices are present in this museual environment. Virtual museums are still creating their identity within the context by which it is defined. It is by trying to understand the role of the virtual museum for the education focus efforts toward this scientific research that helps researchers to scientific knowledge to all who need.